2012
DOI: 10.1021/bi300341j
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding of a β-Cyclodextrin Dimer to the Amyloid β Peptide Modulates the Peptide Aggregation Process

Abstract: Alzheimer's disease involves progressive neuronal loss. Linked to the disease is the amyloid β (Aβ) peptide, a 38-43-amino acid peptide found in extracellular amyloid plaques in the brain. Cyclodextrins are nontoxic, cone-shaped oligosaccharides with a hydrophilic exterior and a hydrophobic cavity making them suitable hosts for aromatic guest molecules in water. β-Cyclodextrin consists of seven α-d-glucopyranoside units and has been shown to reduce the level of fibrillation and neurotoxicity of Aβ. We have stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 49 publications
(134 reference statements)
4
38
0
Order By: Relevance
“…Additionally, β-CDs have been reported to be able to directly bind Aβ [69][70][71], and substantially decrease its neurotoxic effect in vitro. Another β-CD derivative, the per-6-alkylamino-β-CD, has been shown to interfere with the oligomerization process of Aβ 1-42 responsible in part for Aβ neurotoxicity [79].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Additionally, β-CDs have been reported to be able to directly bind Aβ [69][70][71], and substantially decrease its neurotoxic effect in vitro. Another β-CD derivative, the per-6-alkylamino-β-CD, has been shown to interfere with the oligomerization process of Aβ 1-42 responsible in part for Aβ neurotoxicity [79].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The neuroprotection by CyD has been reported in vivoi n the case of neurodegenerative diseases. [14] In particular, b-CyD is able to interact with Ab 1-40 amyloid peptide at sites Y10, F19, and/or F20 [15] and decrease substantially the neurotoxic effects of Ab in vitro [16,17] and in vivo. [18] Interestingly, b-CyD acts in synergyw ith curcumin to suppress a-synuclein aggregation (involved in Parkinson's disease) and breaks up the preformed aggregates almost completely.…”
Section: Introductionmentioning
confidence: 99%
“…According to the revised amyloid-cascade hypothesis, certain types of soluble Aβ oligomers and protofibrils are more toxic than Aβ fibrils and correlate well with dementia [14], [15], [16], [17]. Therefore, modulation of Aβ aggregation using small molecules is considered a promising way to eliminate Aβ associated toxicity [3], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. We recently reported that red food dye erythrosine B (ERB) is a novel modulator of Aβ-aggregation in vitro and Aβ neurotoxicity [33].…”
Section: Introductionmentioning
confidence: 99%